DEVELOPMENT OF AN ONLINE LEARNING MODULE FOR SYSTEMS OF LINEAR EQUATIONS IN TWO VARIABLES (SPLDV) ASSISTED BY THE DESMOS WEB PLATFORM - Salsabila, Dian Alhira (Jurnal Pendidikan Matematika dan IPA, 2026)
This is a research and development (R&D) that produce a learning module, on the topic of SPLDV in class VIII at SMP Negeri 1 Remboken. The module was developed by using the ADDIE method. We obtain that the learning module satisfies the criteria of validity, effectiveness and practicality. The results of the learning module validity from the experts of the topics is 4.56 and from media experts is 4.48. This satisfy the very valid category. By using the modul we obtained the average student learning outcomes test is 80.45 with a percentage of completeness of 90.91%, which is a very effective category. Teacher’s assessment of the module is 4.27 which is a very practical category, and the students respons is very positive category. By this, we conclude that by using the learning module on the SPLDV topic for class VIII students at SMP Negeri 1 Remboken, students readiness and understanding in the learning process can develop well.